(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Electric vehicles have insignificant working costs since they have less moving parts to keep up with, and they are additionally exceptionally eco-accommodating in light of the fact that they consume practically zero non-renewable energy sources. With the improvement of new advancements in the present quick moving world, the utilization of oil and gas has expanded significantly, bringing about issues, for example, a worldwide temperature alteration, environmental change, unrefined petroleum deficiencies, etc. Vehicle organizations have started exploration to make Electric Technology valuable in regular day to day existence because of these variables. Electric vehicle drives have many advantages over conventional gas powered motors, including diminished neighborhood contamination, further developed energy effectiveness, and less dependence on oil. Be that as it may, there are significant road obstructions to the far reaching reception of electric vehicles, including battery mechanical cutoff points, high buying costs, and an absence of charging foundation. This paper is based on an explanation of electric car efficiency, technology, architecture, as well as safety. The paper finishes by discussing the benefits and drawbacks of electric cars, as well as how this technology will take over the globe in the future and become a viable alternative to gasoline and diesel vehicles.